Perceptions and attitudes of stakeholders on the return of brown bears (Ursus arctos): contributions from a workshop held in northern Portugal - Azevedo, João (2023)
Brown bears (Ursus arctos) were extinct in Portugal by 1843. In the spring of 2019, a male bear was officially confirmed in northern Portugal, and more bears will likely reach the country shortly. We surveyed participants in a workshop held in Bragança in October 2021 to understand the perceptions and attitudes of different stakeholder groups (Administration, Research, Nongovernmental Organizations, and Local Stakeholders) regarding the return of brown bears to Portugal. Results indicate that, generally, participants would feel safe in areas where bears are present, are positive toward the return of brown bears, and see it as an opportunity for local development rather than a threat. Results also indicate a high level of consensus among groups of stakeholders concerning the issues analyzed. These preliminary results provide a baseline for perceptions and attitudes to consider when planning the conservation of brown bears returning to Portugal.